Pengaruh Harga Dan Diferensiasi Produk Terhadap Keputusan Pembelian Pada Rumah Makan Sagala Sunda - Annisa Febriyanti; Netti Nurlenawati; Dexi Triadinda (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The aim of this research is to determine the partial and simultaneous influence of price and product differences on purchasing choices at the Sagala Sunda Restaurant. This research method uses quantitative, which is based on certain groups or samples based on the principles of positivism. The research population consisted of customers who ate at the Sagala Sunda Restaurant, resulting in a sample size of 150 people. Data examination includes instrument analysis to assess validity and reliability, classical assumption tests such as normality tests, heteroscedasticity tests, and multicollinearity tests, hypothesis tests such as t tests and F tests, multiple linear regression analysis, and calculating the coefficient of determination. The findings from this research show that price and product differentiation have a positive and significant effect on purchasing decisions at the Sagala Sunda Restaurant. In addition, it is shown that these two variables together contribute 78.5% of the impact on purchasing decisions.